A educação infantil e os eventos de letramentos em uma turma de 5 anos - Isabela Costa Dominici (2014)
Which is the interest of 5 years old children on literacy? Which cultural artefacts are essential for assigning meanings on literacy by children? At what time, where and when children manifest these interests? These and other questions are part of this research that aimed to investigate the meanings assigned by children of 5 years old to literacy events. For therealization of this research guided ourselves by ontologica l and epistemology conceptions from History-Cultural Psychology and Interactional Ethnography that considers the being as biological, historic, social and cultural. From this proposed dialogue, between History-Cultural Psychology and Interactional Ethnography, we also use the concepts of areas of impending development, language, culture, learning and semiotic mediation. For the construct and data analysis guided ourselves the emic and ethic perspective proposed by InteractionalEthnography and we chose the participant observation as used video recording, field notebook, and interviews with children. This research occurred at Unidade Municipal de Educação Infantil (UMEI) in the city of Belo Horizonte during months from February and July of the year 2013. During the construction and data analysis was identified 121 literacyevents. From these literacy events we emphasize those in which children constructed hypotheses about language and writing language, those that children were protagonists and those that play and drawing were essential for meanings construction for writing language. Along analysis of literacy events, are evidenced in the classroom both autonomous literacies as ideological, as well as made explicit the children´s interest in an appropriating the written language. We completed our discussion arguing that the written learning by 5 years old children has relation with cognition and with affection. We believe that learning this languagecan provide the construction of new knowledge as well as new identities. We also noted that role of personal and social experiences of children are constituents of meanings they have given to the literacies events.